Physiological factors influencing climate-smart agriculture: Daylength-mediated interaction between tillering and flowering in rice - Hyeon-Seok Lee; Ju-Hee Kim; So-Hye Jo; Seo-Yeong Yang; Jae-Kyeong Baek; Yeong-Seo Song; Jung-Il Cho; Jiyoung Shon (BMC Plant Biology)
Abstract Background Controlling rice tillering and flowering is essential for reducing greenhouse gas emissions from paddy fields, a key objective in climate-smart agriculture. However, the interaction between tillering and flowering remains controversial and poorly understood. In this study, we subjected plants of the rice cultivars ‘Saenuri’ and ‘Odae’ to short- and long-day conditions and compared their growth and flowering responses after tiller removal. Results The effects of tiller removal differed depending on daylength conditions. Under short days, plants in the tiller-removal group flowered earlier than the controls, whereas the opposite trend was observed under long days. This response was associated with changes in florigen gene expression. Under short days, the expression of Hd3a, which promotes flowering, increased in the tiller-removal group compared with that in the controls. In contrast, under long days, the expression of OsMFT1, a gene that delays flowering and promotes spikelet formation, was significantly upregulated, leading to an increased spikelet number. Notably, spikelets per panicle in the tiller-removal groups increased approximately 3.4-fold in ‘Saenuri’ and 2.2-fold in ‘Odae’ under long-day conditions compared with those in their respective controls. Conclusions These findings highlight the daylength-dependent variability in tillering and flowering interactions, providing new insights into their regulatory mechanisms. This study offers a foundation for optimizing rice growth strategies under varying photoperiod conditions, contributing to climate-smart agricultural practices and improved breeding programs.